PERANCANGAN ALAT MONITORING ZAT LARUTAN DALAM AIR HIDROPONIK BERBASIS ARDUINO - Stevent; Sunarsan Sitohang (Computer Science and Industrial Engineering, 2024)
Nowadays people have trouble farming, because of the limited of spots, so Hyrdoponic was invented, hydroponic is an agriculture technique that replaces dirt as a planting medium with a water-based nutrient solution. In the hydroponic process, every farmer needs to monitor some parameters like TDS Rate, Temperature, and pH in most cases people like to use the old method of monitoring, some problem that we got from the old method is, farmers need to bring measuring tools for every parameter, we will create a monitoring system based on Arduino that farmer can access from distances with using platform name Blynk by internet, for research we using the waterfall method. The result of the research is a monitoring system with Arduino that can connect to a smartphone with the Blynk app on the Internet. We design the UI as simple as possible for farmers that not good at technology can use it easily, the goal of this research is make a product that can monitor hydroponic water tank, the hope we can make monitoring process being fast and easy .